Implementasi Media I-Board dalam Meningkatkan Keaktifan Siswa pada Pembelajaran PAI - Firdaus Firdaus; Faiz Fahrudin; Friosa Alfrianto; Ana Isma Wardani (Halaqa: Journal of Islamic Education, 2026)
This study aims to evaluate the effectiveness of using I-Board (Islamic Board Game) as an instructional innovation to enhance student participation in Islamic Religious Education (PAI) at SMK Muhammadiyah 2 Ajibarang. The background of this study is based on the low level of student engagement in traditional and monotonous PAI teaching methods. I-Board was designed as an interactive learning medium capable of creating a collaborative, positively competitive, and enjoyable learning atmosphere. This research employed a descriptive qualitative approach, with data collection techniques including observation, in-depth interviews, and documentation. The research subjects consisted of PAI teachers and students from classes that implemented the I-Board media. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing, following the model proposed by Miles and Huberman. The findings indicate that the implementation of I-Board effectively improves both the quality and quantity of student participation, as evidenced by increased involvement in asking questions, providing answers, participating in discussions, and actively engaging in the learning process. Furthermore, this media assists teachers in managing the classroom in a more dynamic and interactive manner.